Scribal practice, manuscript production and the transmission of music in late medival France: the manuscripts of Guillaume de Machaut - Earp, Lawrence Marshburn (Michigan University microfilms international, 1983)
Dissertation presented to the Faculty of Princeton University in candidacy for the degree of Doctor of Philosophy recommended for acceptance by the Department of Music, june 1983